Understanding the role of augmented reality in enhancing students’ emotions in tourism online learning: a pleasure-arousal-dominance perspective / Silverina A. Kibat, Anderson Ngelambong and Mohd Raziff Jamaluddin - Kibat, Silverina A.; Ngelambong, Anderson; Jamaluddin, Mohd Raziff (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The emergence of online learning has revolutionized higher education institutions by providing students with access to flexible and convenient learning options. However, there are challenges to online learning, such as the lack of physical interaction, which leads students to become bored and lose focus. While augmented reality has the potential to improve students' learning experiences by delivering immersive and interactive content, there has been little research into the potential of augmented reality in enhancing students' emotional experiences in online learning. The study aims to explore undergraduate students' emotional responses to augmented reality technology in online learning using the Pleasure-Arousal-Dominance framework. Based on the thematic analysis, it was found that most students agreed that online learning can be boring, sleepy, and demotivating if not delivered effectively. The study found that by integrating augmented reality into online teaching, it can provide more enjoyable, exciting, and pleasureful learning experiences. Thus, from a practical standpoint, it is suggested that augmented reality technology should be promoted in universities to improve online teaching delivery. Theoretically, this study has broadened the existing understanding of augmented reality mechanisms that can enhance online learning experiences. Several study limitations are discussed at the end of the paper as references and suggestions for future research.